Prader-Willi syndrome: a nest for premature coronary artery disease?. (7th February 2018) - Brás, Diogo Rodrigues; Semedo, Pedro; Piçarra, Bruno Cordeiro; Fernandes, Renato
Abstract : Individuals affected by Prader-Willi syndrome (PWS) may show increased risk for coronary artery disease (CAD), which probably relates, at least, with high burden of cardiovascular risk factors. A 27-year-old man with PWS, obesity, hypertension, diabetes mellitus and dyslipidaemia attended the emergency department with complaints of flu-like condition and chest pain. The ECG revealed a mild ST-segment elevation in inferior leads, followed by positive myocardial necrosis biomarkers. Attending to the high cardiovascular risk profile, ST-segment elevation in inferior territory and wall motion abnormalities, a coronary angiogram was performed. The latter showed a three-vessel CAD, 60% stenosis in midanterior descending artery, total occlusion (100%) of the obtuse marginal artery and 99% stenosis with high thrombi burden in the proximal right coronary artery. The present case report emphasises the plausibility of premature CAD in patients with PWS, a possible underdiagnosed feature of this condition.